The danger of landslide activity in the Mozdok region of Republic of North Ossetia-Alania - V. V. Razumov; N. D. Bogdanova; N. V. Razumova; V. A. Shalnev (Наука. Инновации. Технологии)
The object of the study is landslide activity in the Mozdok administrative region of the Republic of North Ossetia-Alania. The work examines the results of systematization and analysis of various sources containing information about the activity and danger of landslide processes in this area in the 21st century. The conditions, causes, activity and danger of landslide activations in the region are characterized. It is noted that the activity of landslide processes in the study area is mainly due to natural factors, however, recently the emergence of new landslide forms and the activation of old ones most often occur under technogenic influence. Landslide activity in the region is observed on the ledge of the right bank alluvial-accumulative terrace of the river. Terek, where most of the settlements of the region are located, as well as the northern slope of the Tersky ridge and in the area of the watershed ridge of the Sunzhensky ridge. The most significant activation of landslide processes (causing deformation of residential buildings and roadways of streets) was observed in the villages of Maly Malgobek, Predgornoye and Sukhotskoye. Since 2021, after the reconstruction of the Zilga – Mozdok highway, significant landslide deformations and destruction of the roadway have been observed on the section of the road between the villages of Khurikau (Mozdok district) and Old Batako (Right Bank district). The article provides information about the activity of landslide activity and the scale of deformations and destruction of residential and transport infrastructure that occurred in the area. Analysis of the socio-economic consequences of the landslide activations shows a significant degree of their danger to the life of the population in the Mozdok region.